Roslyn cookbook : compiler as a service, static code analysis, code quality, code generation, and more - Vasani, Manish (Packt Publishing, 2017)
Use Roslyn as a service to write powerful extensions and tools and use them in Visual Studio to improve code quality and maintain your source code more effectively. About This Book Use Roslyn extensions and tools in Visual Studio to enforce "house rules" on code and fix security and performance vulnerabilities in your code. Write Roslyn extensions using the Roslyn service API to help developers enforce conventions and design idioms. Improve developer productivity by using Roslyn-based agile development features in Visual Studio, such as live unit testing, C# interactive and scripting. Contribute to the C# language and compiler tool chain to analyze and edit code. Who This Book Is For .NET Developers and architects, who are interested in taking full advantage of the Roslyn based extensions and tools to improve the development processes, will find this book useful. Roslyn contributors, i.e. the producers and C# community developers, will also find this book useful What You Will Learn Write extensions to analyze source code and report warnings and errors. Edit C# source code to fix compiler/analyzer diagnostics or refactor source code. Improve code maintenance and readability by using analyzers and code fixes. Catch security and performance issues by using PUMA scan analyzers and FxCop analyzers. Perform Live Unit tests in Visual Studio. Use C# interactive and scripting in Visual Studio. Design a new C# language feature and implement various compiler phases for a new language feature. Write command line tools to analyze and edit C# code. In Detail Open-sourcing the C# and Visual Basic compilers is one of the most appreciated things by the .NET community, especially as it exposes rich code analysis APIs to analyze and edit code. If you want to use Roslyn API to write powerful extensions and contribute to the C# developer tool chain, then this book is for you. Additionally, if you are just a .NET developer and want to use this rich Roslyn-based functionality in Visual Studio to improve the code quality and maintenance of your code base, then this book is also for you. This book is divided into the following broad modules: Writing and consuming analyzers/fixers (Chapters 1 - 5): You will learn to write different categories of Roslyn analyzers and harness and configure analyzers in your C# projects to catch quality, security and performance issues. Moving ahead, you will learn how to improve code maintenance and readability by using code fixes and re...